2017
DOI: 10.1002/1873-3468.12737
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN31 is a critical regulator on transduction of survival and apoptotic signals in hepatocellular carcinoma cells

Abstract: Tetraspanins are commonly believed to act as 'molecular facilitators', not directly involved in signal transduction. Tetraspanin 31 (TSPAN31), recently discovered to be linked to cancer, has not yet been studied in hepatocellular carcinoma (HCC). Here, we show that TSPAN31 is the natural antisense transcript of cyclin dependent kinase 4 (CDK4), and regulates the expression of CDK4 mRNA and protein. Target analysis indicates that miR-135b can directly regulate TSPAN31 expression. miR-135b-induced TSPAN31 silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…PI3K/AKT/mTOR pathway occupies a central position in the network of dysregulated signaling pathways in HCC. Inhibiting PI3K/AKT/mTOR can prevent abnormal cell proliferation, cellular metabolism, and tumor angiogenesis, thus providing potential molecular targeted therapeutics . Considering the important role of PI3K/AKT/mTOR signaling pathway in HCC, we examined the phosphorylation of AKT and mTOR, and found that PRDM8 exhibited its antitumor activities through PI3K/AKT/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT/mTOR pathway occupies a central position in the network of dysregulated signaling pathways in HCC. Inhibiting PI3K/AKT/mTOR can prevent abnormal cell proliferation, cellular metabolism, and tumor angiogenesis, thus providing potential molecular targeted therapeutics . Considering the important role of PI3K/AKT/mTOR signaling pathway in HCC, we examined the phosphorylation of AKT and mTOR, and found that PRDM8 exhibited its antitumor activities through PI3K/AKT/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…NATs is a highly heterogeneous group of lncRNAs, transcribed from the complementary chain of target genes in an antisense orientation, that regulate post‐transcriptionally gene expression via RNA:RNA interactions with mRNA or miRNAs [196]. In this sense, oncogenic lncRNA FOXD1‐AS1 (FOXD1‐antisense 1), the antisense transcript of the gene FOXD1, was reported to interact with miR339‐5p and miR342‐3p [197], tumor suppressor TP73‐AS1 sponged miR‐941 [198], while TSPAN31, the natural antisense transcript of cyclin dependent kinase 4 (CDK4), interacted with miR‐135b in hepatocellular carcinoma causing TSPAN31 silencing and the subsequent upregulation of CDK4 [199].…”
Section: Long Non‐coding Rnas (Lncrnas) and Their Functional Relationmentioning
confidence: 99%
“…The tetraspanin family facilitates hepatoma promotion by activating proliferation and anti-apoptotic properties of HCC cells. Some tetraspanins, such as TSPAN15, can enhance tumor cell proliferation ability (28), while other family members, such as CD9, CD63, TSPAN1, TSPAN7, and TSPAN31, can antagonize apoptosis and facilitate tumor cell survival (29)(30)(31). These two effects act together in promoting the development of tumors (Figure 1).…”
Section: Role Of Tetraspanins In Hcc Cell Growth and Survivalmentioning
confidence: 99%